Produksi Benih Jagung Hibrida Pioner 8050 (Corteva) dengan Rasio Tanam 5:1 di Desa Kanigoro Kecamatan Kanigoro Kabupaten Blitar - Juli Santoso; Nirmala Aulia Sari; Moh Yasin; Vergiliano Haumen Colo; Novita Dyah Safitri; Ahmad Faris Al Mubarok (Fakultas Pertanian, Universitas Darul Ulum, 2025)
Hybrid maize seed production requires specific cultivation and management techniques that differ from commercial maize production, particularly in regulating the ratio of male and female plants to ensure effective cross-pollination and genetic purity. This study aimed to describe the implementation of hybrid maize seed production of Pioner 8050 (Corteva) using a 5:1 female-to-male planting ratio in Kanigoro Village, Kanigoro District, Blitar Regency, Indonesia. The research employed a descriptive field-study approach conducted on approximately 100–120 ha of seed production land managed by farmer groups under a partnership scheme with a seed company. Data were collected through direct field observations and structured interviews focusing on planting ratio arrangement, detasseling practices, fertilization, pest and disease management, irrigation systems, and partnership mechanisms. The results showed that the application of a 5:1 planting ratio effectively optimized land use while ensuring adequate pollen availability for cross-pollination. Zero tillage practices, balanced fertilization using urea and NPK, integrated pest and disease management, and controlled detasseling contributed to maintaining genetic purity and seed quality. The partnership system facilitated farmers’ access to production inputs, technical guidance, and assured market absorption. Productivity reached 6–7 tons ha⁻¹ of fresh ears, with harvested kernels exhibiting appropriate physiological maturity, moisture content, and high viability. Overall, the hybrid maize seed production system implemented in Kanigoro Village demonstrates a technically effective and institutionally supported model that can be replicated in other regions to enhance sustainable hybrid maize seed development and strengthen national seed supply systems.